Neuropsychological Research in Obsessive-Compulsive Disorder: Current Status and Future Directions - Kashyap, Himani; Abramovitch, Amitai (Frontiers in Psychiatry, 2021)
Neuropsychological functions in obsessive-compulsive disorder (OCD) have been extensively investigated. Despite some common findings across studies indicating deficient test performance across cognitive domains with small to medium effect sizes, results remain inconsistent and heterogeneous. However, multiple past attempts to identify moderators that may account for such variability have been unrewarding. Typical moderators including symptom severity, age at onset, medication status and comorbid conditions failed to provide sufficient explanatory power. It has then been posited that these inconsistencies may be attributed to the inherent heterogeneous nature of the disorder (i.e., symptom dimensions), or to the natural fluctuation in symptom severity. However, recent meta-analyses suggest that these factors may not account for the persistent unexplained variability. Other potential factors – some of which are unique to neuropsychological testing – received scarce research attention, including definition of cognitive impairments, specificity and selection of test and outcome measures, and their limited ecological validity. Other moderators, particularly motivational aspects, and metacognitive factors (e.g., self-efficacy) were not previously addressed despite their potential association to OCD, and their documented impact on cognitive function. The aim of the present mini-review is to provide an updated succinct overview of the current status of the neuropsychological literature in OCD and expanding upon oft-neglected potential moderators and their putative impact on neuropsychological findings in OCD. Our goal is to highlight important avenues for further research and provide a road map for investigators in order to advance our understanding of cognitive functions in OCD that has been stagnant in the past decade.